Investigation of the synergistic effect of the Fenton process on the paint industry wastewater treatment and optimization of independent process parameters - Apaydin, Omer; Kurt, Ugur; Ilhan, Fatih (ELSEVIER SCIENCE INC, 2023)
Paint industry wastewater is hard to treat due to its complex and changing structure. In the study, the Fenton oxidation process was used to treat this wastewater. The pH levels required for the Fenton process were obtained without any chemical addition other than Fenton's catalyst and oxidant. Reaction time, H2O2 concentration, and Fe2+ concentration were chosen as independent parameters for the experimental design employing Taguchi orthogonal arrays. These independent parame-ters were varied at four different levels to find out their effects on the removal efficiencies of the dependent parameters. Chemical oxygen demand (COD) and color were chosen as the dependent parameters. The removal efficiencies of COD and color were obtained at 69% and 98%, respectively. According to optimization studies, the degree of effect of H2O2 concentration, Fe2+ concentration, and reaction time on COD removal performance were obtained as 12.01%, 23.87%, and 21.67%, respectively. Moreover, the degree of effect on color removal performance of H2O2 concentration, Fe2+ concentration, and reaction time were obtained as 15.08%, 19.00%, and 22.42%, respectively. Furthermore, the results from this experimental optimization study show that the synergistic effect of Fenton oxidation on COD removal provides additional removal efficiency reaching 190% compared with H2O2's real oxidation potential.
Keywords: Fenton process; Optimization; Paint industry wastewater; Synergistic effect; Treatability; ELECTROCHEMICAL TREATMENT; ELECTRO-FENTON; COLOR REMOVAL; ELECTROCOAGULATION; COAGULATION; DEGRADATION; ACID; COAGULATION/FLOCCULATION; CARBON; REUSE; Engineering; Water Resources